The Association of Nurses : Application for Membership
1937 1937 1930s 1 page Org. of nurses. THE ASSOCIATION OF NURSES HOSPITALS and public authorities are showing profound concern at the present state of the nursing services, and especially the reluctance of young people to enter the profession. While conditions in all other spheres of life have steadily changed and evolved, the nursing profession has not kept pace with modem demands. Interested outside bodies can undoubtedly give valuable help in solving this problem, but the duty of modernising their profession must be undertaken primarily by the nurses themselves. THE ASSOCIATION OF NURSES aims at improving the status of nurses, to enable them adequately to discharge their responsibilities to the patient under the complex conditions of modern medical treatment. Desirable recruits are being repelled by outworn restrictions, long hours, lack of opportunity for social and cultural activity, low pay and poor prospects. The Association will work, by methods of persuasion and the education of public opinion, to secure adequate freedom, leisure and remuneration for nurses, a high standard of professional qualification and conduct, and wider opportunities for service. The Association will willingly co-operate with any other bodies having similar aims. THE PROPOSALS contained in the Nurses' Charter of the Trades Union Congress seem to offer a suitable basis for a nurses' programme, and the Association will join in any endeavour to get the Charter carried into effect. MEMBERSHIP is open to all qualified nurses and and probationers working for a recognised qualification, and the subscription is 8d. per month. The Association hopes to achieve the position in the nursing world that the British Medical Association has won among doctors. APPLICATION FOR MEMBERSHIP I wish to become a member of The Association of Nurses. Name (in full).............................................................................................. 193... Address Place of Work (if not at above address) Status and Qualifications (if Probationer state in what year) Are you a member of any other nursing organisation? After completing this form please post it to the Secretary, The Association of Nurses, Miss Thora Silverthorne, S.R.N., 12, Great Ormond Street, London. W.C.1 HOLBORN 5339 or hand it to the person named below Signature of introducer .......... 292/54.73/2/67